Faculty Development as Community Building - Eib, B. J.; Miller, Pam (International Review of Research in Open and Distributed Learning, 2006)
When faculty development is viewed as an ongoing need and when we approach faculty development as a long-term, continuous effort, community building becomes a part of the process. Carefully designed faculty development approaches can facilitate and create a culture that supports a thoughtful focus on teaching, while at the same time, nurture a sense of connectedness and collegiality across the organization that is vital to continuous innovation and improvement. This paper reports on a program designed to improve the collegial culture at a higher educational organization in Western Canada. While the program was aimed at a Social Work Faculty at a research university, we believe the design can be modified and applied in other disciplines and in other environments, such as distant and open universities. We conclude with suggestions for applying our approach to faculty development in open and distance institutional contexts.